High-yield and Functional IgY Anti-S1 SARS-CoV-2 Delta Variant from Chicken Immunized with In-house Recombinant Protein - Kamaluddin Zarkasie; Teridah Ernala Ginting; Andrea Hynan Poeloengan; Febi Andriani; Aksar Chair Lages; Vina Cornelia; Anggah Nugraha; Bustanur Rosidi; Setyarina Indrasari; Chairul Anwar Nidom; Irawan Yusuf (Indonesian Biomedical Journal)
BACKGROUND: During COVID-19 pandemic, effective preventive and therapeutic strategies was urgently necessary, especially with the emerging Delta variants. Previous existing interventions have some limitations, and passive immunization using immunoglobulin Y (IgY) is considered viable. However, the potential of IgY antibodies remains underexplored locally. Therefore, a feasible study was conducted to produce IgY against the SARS-CoV-2 Delta variant from chickens raised on a farm, instead of a laboratory environment, by using in-house recombinant protein, to offer a promising low-cost alternative for passive immunization.